ZERO-VOLTAGE SWITCHING SOLUTIONS IN SINGLE-ENDED FORWARD TOPOLOGIES OVER ANY OPERATING CONDITIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
In this paper, a novel solution is presented to enable zero-voltage switching (ZVS) under any operating condition, utilizing transformers with extremely low leakage inductance. The proposed methods ensure that the primary switches turn on at zero voltage while the secondary rectifiers turn off at zero current. While numerous ZVS techniques for single-ended forward topologies have been proposed over the years, most rely on transformer leakage inductance to delay the current flow to the secondary. Although these approaches achieve zero-voltage switching (ZVS) for the primary switches, they fail to achieve zero-current switching (ZCS) in the secondary rectifiers. Additionally, a larger leakage inductance reduces the effective duty cycle, often necessitating a turns ratio adjustment to maintain regulation at the minimum input voltage. This adjustment increases the primary RMS current and higher voltage stress in the secondary. In contrast, this paper presents a ZVS solution specifically designed for forward converters with low leakage inductance, making it particularly suitable for wide input voltage ranges, high-current applications, and high-frequency operation.
Keywords: Single ended forward topology; Zero-voltage switching; Single-ended forward with active clamp; Two transistors forward